Effect of Food Mass in the Gut on the Metabolic Rate of Carcinus maenas in the Field - David L. Neu; Laura S. Fletcher; Mikayla Bolander; Vibalia Raj; Bailey N. Marlow; Blaine D. Griffen (Ecology and Evolution)
ABSTRACT Numerous laboratory studies have shown that meal size can influence the metabolism of individual organisms. However, in nature, meal size can vary simultaneously with a host of other factors that are often controlled under experimental conditions (e.g., reproductive state, health or physiological condition, temperature, meal composition, etc.). This study examines the influence of the mass of food in the gut (i.e., a proxy for meal size) on the metabolic rate of the European green crab (Carcinus maenas) in the field when other factors are not controlled in order to examine the relative influence of meal size on postprandial metabolism (i.e., specific dynamic action or SDA) compared to other factors known to influence metabolism. We collected 383 crabs intertidally during low‐tide periods and measured their metabolic rates in situ, followed by dissection to assess the mass of food in the gut, as well as reproductive and body condition metrics. We found that metabolic rate increased with body mass and with the mass of food in the gut, and decreased with gravid individuals. Our results show that SDA has an effect that can be observed despite leaving other influential factors uncontrolled, demonstrating the importance of the costs of digestion to the everyday energy balance of these organisms.